Potentiating the Activity of Nisin against Escherichia coli - Zhou, Liang; van Heel, Auke J.; Montalban-Lopez, Manuel; Kuipers, Oscar P. (Frontiers in Cell and Developmental Biology, 2016)
Lantibiotics are antimicrobial (methyl) lanthionine-containing peptides produced by various Gram-positive bacteria. The model lantibiotic, nisin, binds lipid II in the cell membrane. Additionally, after binding it can insert into the membrane creating a pore. Nisin can efficiently inhibit the growth of Gram-positive bacteria and resistance is rarely observed. However, the activity of lantibiotics is at least 100-fold lower against certain Gram-negative bacteria. This is caused by the fact that Gram-negative bacteria have an outer membrane that hinders the peptides to reach lipid II, which is located in the inner membrane. Improving the activity of lantibiotics against Gram-negative bacteria could be achieved if the outer membrane traversing efficiency is increased. Here, several anti-Gram-negative peptides (e.g. apidaecin 1b, oncocin), or parts thereof, were fused to the C-terminus of either a truncated version of nisin containing the first three/five rings or full length nisin. The activities of these fusion peptides were tested against Gram-negative pathogens. Our results showed that when an 8 amino acids (PRPPHPRL) tail from apidaecin 1b was attached to nisin, the activity of nisin against Escherichia coli CECT101 was increased more than two times. This research presents a new and promising method to increase the anti-Gram-negative activity of lantibiotics.